Rekonstruksi Kedudukan Ahli Waris Anak Angkat: Mengisi Kekosongan Norma Hukum Waris Nasional Berbasis Keadilan Substantif - I Dewa Ketut Wahyu Dwikarna; Komang Febrinayanti Dantes (International Forum of Researchers and Lecturers, 2026)
This study examines the legal uncertainty regarding the status of adopted children as heirs within Indonesia’s pluralistic national inheritance legal system. The Civil Inheritance Law (KUH Perdata), Islamic Inheritance Law (KHI), and Customary Inheritance Law each regulate adopted children differently and incompletely, thereby creating a legal vacuum. that harms adopted children socially and emotionally. This study aims to analyze the weaknesses of these three legal systems and formulate a reconstruction of the status of adopted children based on substantive justice. Using a normative approach and the theories of legal reconstruction, substantive justice, and legal certainty, this study finds that reconstruction can be achieved through strengthening the mandatory will (wasiat wajibah), revising Article 209 of the KHI, and codifying and unifying national inheritance law through an Omnibus Law model. The parameters of justice used include the best interests of the child, public welfare, and non-discrimination. In conclusion, the reconstruction of the status of adopted children as heirs is urgently needed to fill the gaps in national inheritance law in a just manner.